Joint Associations of Residential Density and Neighborhood Involvement With Physical Activity Among a Multiethnic Sample of Urban Adults. (August 2015) - Johnson-Lawrence, Vicki; Schulz, Amy J.; Zenk, Shannon N.; Israel, Barbara A.; Wineman, Jean; Marans, Robert W.; Rowe, Zachary
Regular physical activity is associated with improvements in overall health. Although resident involvement in neighborhood social activities is positively associated with physical activity, neighborhood design features, including residential density, have varied associations with physical activity. Using data from a multiethnic sample of 696 adults in Detroit, Michigan, multilevel models were used to examine joint effects of residential density and resident involvement in neighborhood activities in relation to physical activity. We found a marginally significant negative interaction of higher residential density and resident neighborhood involvement. Higher residential density was negatively associated with physical activity, and resident neighborhood involvement was positively associated with physical activity. Our findings suggest that future work incorporate additional neighborhood and individual-level characteristics to understand the complexity of the association between the neighborhood environment, resident social engagement in the neighborhood, and physical activity.